Fiscal Policy Rules - Kopits, George (Occasional Papers; Occasional Paper ;, 1998)
What are fiscal policy rules? What are the principal benefits and drawbacks associated with various fiscal rules, particularly compared with alternative approaches to fiscal adjustment? Can fiscal rules contribute to long-run sustainability and welfare without sacrificing short-run stabilization? If so, what characteristics of fiscal rules make this contribution most effective? And in what circumstances and contexts, if any should the IMF encourage its member countries to adopt fiscal rules? This paper seeks to identify sensible fiscal policy rules that can succeed, if chosen by a member country, as an alternative to descretionary fiscal rules.